Peranan Hukum Paten terhadap Peneliti Indonesia pada Era Liberalisasi Perdagangan - Aunur Rohim Faqih (Jurnal Hukum IUS QUIA IUSTUM, 2002)
In free tradeera, the intellectual property lights issue isgetting progress. In this context, every person mustbe abletogain advantages from this issue. For Indonesian researchers, they would beable togain the advantages from patent. It is influenced that patent is more concern with characteristics of science and technological development. This is the core of patentutilities for researchers in Indonesia viewed from the law aspect.